Performance of Channel Estimation Technique in MIMO-OFDM System Using mPSK Modulation - ., Musayyanah; Moegiharto, Yoedy; Puja Astawa, I Gede (EMITTER International Journal of Engineering Technology, 2013)
Multicarrier modulation technique as Orthogonal Frequency Division Multiplexing (OFDM) is able to vanishIntersymbol Interferences (ISI) caused by multipathchannel. Merging with multi- antenna transmission techniques such asMIMO become MIMO- OFDM system is able to improve (data rate transmission)the transmission of data and capacity of the system. Pilot channel estimation technique with the algorithm Linear Minimum Mean Square Error (LMMSE) with modulation m-PSK is applied in this study. The results obtained in the form of graphs BER against EbNo which shows that the system performance with LMMSEestimator has a different gain for QPSKmodulation better about 0.75 dB, for 8 PSKmodulation is about 1.5 dB and for 16 PSKmodulation around 1 dB compare to LS estimator. Number of the largest antenna both in the transmitter and receiver produce the best system performance. Observation for QPSKmodulation shows a scheme transmitter- receiver antenna 4x2 having gain approximately 9 dB better than the number of the lowest transmitter antenna(1x2). For scheme 4x4 shows gain around 8,5 dB than the number of the lowest receiver antenna.Keywords:MIMO, OFDM,LS, LMMSE, MPSK.